2021
DOI: 10.1111/cxo.13092
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use as a possible risk factor for myopia

Abstract: Clinical relevance: This study demonstrates an association between myopia and smartphone data usage. Youths now spend more time participating in near tasks as a result of smartphone usage. This poses an additional risk factor for myopia development/progression and is an important research question in relation to potential myopia management strategies. Background: Children are now exposed to another possible environmental risk factor for myopiasmartphones. This study investigates the amount of time students spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 42 publications
4
99
0
2
Order By: Relevance
“…In addition, the heterogeneity was high in the meta-analysis of included cross-sectional studies. First, a large number of studies have identified potential risk factors that may result in visual impairment, which included both genetic and environmental factors [ 20 , 26 , 56 , 58 ] such as age [ 26 ], education and occupation [ 58 ], outdoor activity [ 20 , 58 ], and parental myopia [ 20 ]. However, some studies did not include these variables in the multivariate analysis, which might contribute to the inconsistent findings, and might further affect the individual effect estimates and the pooled OR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the heterogeneity was high in the meta-analysis of included cross-sectional studies. First, a large number of studies have identified potential risk factors that may result in visual impairment, which included both genetic and environmental factors [ 20 , 26 , 56 , 58 ] such as age [ 26 ], education and occupation [ 58 ], outdoor activity [ 20 , 58 ], and parental myopia [ 20 ]. However, some studies did not include these variables in the multivariate analysis, which might contribute to the inconsistent findings, and might further affect the individual effect estimates and the pooled OR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study (N=1153 participants) using stratified random cluster samples did not find a statistically significant association between smartphone use time and myopia [ 25 ]. Similarly, a study conducted in Ireland (N=418 participants) indicated that smartphone use time was not a risk factor for myopia [ 26 ]. Toh et al [ 27 ] found that smartphone use time was associated with an increased risk of visual symptoms (ie, blurring of vision, dry eye), but a decreased odds of myopia.…”
Section: Introductionmentioning
confidence: 99%
“… 17 A study of 418 students found that device recorded smartphone data usage, an objective surrogate for time spent using the smartphone, was independently associated with myopia in a study of 418 students (OR1.08, 95% CI 1.03-1.14). 18 …”
Section: Global Tightening Of Infection Control Measuresmentioning
confidence: 99%
“…While some studies reported a significant association between increased computer and smart phone use time and myopia development 23,24 , a meta-analysis reported s no association of screen time with the prevalence or incidence of myopia 25 . Recent studies have shown that children who increased time spent outdoors (but not indoors) have a lower possibility of incident myopia 26,27 .…”
Section: Introductionmentioning
confidence: 99%